Non-communicable disease risk factors among FELDA's second generation in Chini, Pahang - Kamaruzaman, Nor Azam; Pasi, Hafizah (2017)
Background: There is an upward surge of non-communicable diseases (NCD) in Malaysia contributed by increasing risk factors among younger population Objective :. To evaluate the NCD risk factors among second generation of The Federal Land Development Authority (FELDA) settlers in Chini. Methodology : All 322 FELDA settlers aged between 20 to 40 years old who underwent selection for Titian Kasih program and attended health screening at Klinik Kesihatan Chini from 30th March 2016 to 8th April 2016. Results : Both genders are being equally represented. 38% of the subjects are obese while another 32% are overweight. 23% of them have pre-hypertension and 4% have hypertension. There are significant relationship between female gender with body mass index (BMI) and surprisingly, male gender with systolic blood pressure. Age above 30 years old and higher BMI are significantly associated with hypertension. However, there is no significant relationship between age and BMI. Conclusion : Majority of the young FELDA population particularly woman have obesity/overweight which is higher than our national prevalence. Those who are overweight/obese and aged above 30 years old have higher risk for hypertension. These findings show that health promotion towards practising healthier life style focusing on weight management and regular health screening need to be emphasized among this group of society.